Palynological analysis (Scottish Historical and Archaeological Internet Reports, 2005)
The absence of significant amounts of pollen and/or other microscopic organic remains and the differing amount of microscopic organic remains and the different amounts of microscopic charcoal recording in pollen samples 1, 3 and 4 accord with the results of the thin-section analysis. The presence of organic residues in pollen sample 2 corresponds to the presence of significant amounts of relatively well preserved pollen.